A phantom to simulate organ motion and its effect on dose distribution in carbon ion therapy for pancreatic cancer - Stengl, Christina; Panow, Kathrin; Arbes, Eric; Muñoz, Iván Domingo; Christensen, Jeppe Brage; Neelsen, Christian; Dinkel, Fabian; Weidner, Artur; Runz, Armin; Johnen, Wibke; Liermann, Jakob; Echner, Gernot; et al. (Physics in medicine and biology, 2023)
Objective. Carbon ion radiotherapy is a promising radiation technique for malignancies like pancreatic cancer. However, organs’ motion imposes challenges for achieving homogeneous dose delivery. In this study, an anthropomorphic Pancreas Phantom for Ion-beam Therapy (PPIeT) was developed to simulate breathing and gastrointestinal motion during radiotherapy. Approach. The developed phantom contains a pancreas, two kidneys, a duodenum, a spine and a spinal cord. The shell of the organs was 3D printed and filled with agarose-based mixtures. Hounsfield Units (HU) of PPIeTs’ organs were measured by CT. The pancreas motion amplitude in cranial-caudal (CC) direction was evaluated from patients’ 4D CT data. Motions within the obtained range were simulated and analyzed in PPIeT using MRI. Additionally, GI motion was mimicked by changing the volume of the duodenum and quantified by MRI. A patient-like treatment plan was calculated for carbon ions, and the phantom was irradiated in a static and moving condition. Dose measurements in the organs were performed using an ionization chamber and dosimetric films. Main results. PPIeT presented tissue equivalent HU and reproducible breathing-induced CC displacements of the pancreas between (3.98 ± 0.36) mm and a maximum of (18.19 ± 0.44) mm. The observed maximum change in distance of (14.28 ± 0.12) mm between pancreas and duodenum was consistent with findings in patients. Carbon ion irradiation revealed homogenous coverage of the virtual tumor at the pancreas in static condition with a 1% deviation from the treatment plan. Instead, the dose delivery during motion with the maximum amplitude yielded an underdosage of 21% at the target and an increased uncertainty by two orders of magnitude. Significance. A dedicated phantom was designed and developed for breathing motion assessment of dose deposition during carbon ion radiotherapy. PPIeT is a unique tool for dose verification in the pancreas and its organs at risk during end-to-end tests.
Gesehen am 05.06.2024